Evidence supporting the best clinical management of patients with multimorbidity and polypharmacy: a systematic guideline review and expert consensus. (10th December 2018) - Muth, C.; Blom, J. W.; Smith, S. M.; Johnell, K.; Gonzalez‐Gonzalez, A. I.; Nguyen, T. S.; Brueckle, M.‐S.; Cesari, M.; Tinetti, M. E.; Valderas, J. M.
Abstract: The complexity and heterogeneity of patients with multimorbidity and polypharmacy renders traditional disease‐oriented guidelines often inadequate and complicates clinical decision making. To address this challenge, guidelines have been developed on multimorbidity or polypharmacy. To systematically analyse their recommendations, we conducted a systematic guideline review using the Ariadne principles for managing multimorbidity as analytical framework. The information synthesis included a multistep consensus process involving 18 multidisciplinary experts from seven countries. We included eight guidelines (four each on multimorbidity and polypharmacy) and extracted about 250 recommendations. The guideline addressed (i) the identification of the target population (risk factors); (ii) the assessment of interacting conditions and treatments: medical history, clinical and psychosocial assessment including physiological status and frailty, reviews of medication and encounters with healthcare providers highlighting informational continuity; (iii) the need to incorporate patient preferences and goal setting: eliciting preferences and expectations, the process of shared decision making in relation to treatment options and the level of involvement of patients and carers; (iv) individualized management: guiding principles on optimization of treatment benefits over possible harms, treatment communication and the information content of medication/care plans; (v) monitoring and follow‐up: strategies in care planning, self‐management and medication‐related aspects, communication with patients including safety instructions and adherence, coordination of care regarding referral and discharge management, medication appropriateness and safety concerns. The spectrum of clinical and self‐management issues varied from guiding principles to specific recommendations and tools providing actionable support. The limited availability of reliable risk prediction models, feasible interventions of proven effectiveness and decision aids, and limited consensus on appropriate outcomes of care highlight major research deficits. An integrated approach to both multimorbidity and polypharmacy should be considered in future guidelines. Abstract : Content List – Read more articles from the symposium: "Multimorbidity research at the cross‐roads: developing the evidence for clinical practice and health policy".